A quality improvement project using a problem based post take ward round proforma based on the SOAP acronym to improve documentation in acute surgical receiving. (February 2016) - Dolan, R.; Broadbent, P.
Abstract: Objectives: Ward round documentation provides one of the most important means of communication between healthcare professionals. We aimed to establish if the use of a problem based standardised proforma can improve documentation in acute surgical receiving. Methods: Gold standards were established using the RCSE record keeping guidelines. We audited documentation for seven days using the following headings: patient name/identification number, subjective findings, objective findings, clinical impression/diagnosis, plan, diet status, discharge decision, discharge planning, signature, and grade. After the initial audit cycle, a ward round proforma was introduced using the above headings and re-audited over a seven day period. Results: The pre-intervention arm contained 50 patients and the post intervention arm contained 47. The following headings showed an improvement in documentation compliance to 100%: patient name/identification number vs 96%, subjective findings vs 84%, objective findings vs 48%, plan vs 98%, signature vs 96%, and grade vs 62%. Documentation of the clinical impression/diagnosis improved to 98% vs 30%, diet status rose to 83% vs 16%, discharge decision to 66% vs 16%, and discharge planning to 40% vs 20%. Conclusions: Standardised proformas improve the documentation of post-take ward round notes. This helps to clarify the onward management plan for all aspects of a patient's care and will help avoid adverse events and litigation. This should improve the quality and safety of Patient Care. Highlights: Proformas improved documentation. Clarify management plans. Improve patient safety.